2004
DOI: 10.1523/jneurosci.5007-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Precise On-Response in Posterior Parietal Cortex

Abstract: The activity of neurons in the lateral intraparietal area (LIP) of the monkey predicts the monkey's allocation of spatial attention. We show here that despite being relatively high within the visual hierarchy, neurons in LIP have extremely short and precise visual latencies. Mean latency was 45.2 msec; the timing precision of the onset response was usually better than 4 msec. The majority of neurons had a pause in response after an initial burst, followed by more sustained visual activity. Previous attention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 27 publications
11
93
0
Order By: Relevance
“…Consistent with previous research (Bisley et al, 2004), the LIP population responses for both Target-In and Target-Out trials exhibited a very short latency of 47.5 ms. More importantly, both SUA and MUA discriminated between Target-In and Target-Out trials as early as 52.5 ms after stimulus onset (t test on the average SUA and MUA separately, p Ͻ 0.05), in line with the 50 ms selectivity latency of the fastest LIP neurons recorded by Buschman and Miller (2007). Our short population latencies were confirmed by calculations of the neural selectivity latencies (Target-In versus Target-Out) of individual recording sites (t tests on 20 ms bins): the fastest LIP neurons (fifth percentile) showed selectivity latencies of 50 ms [median selectivity latency: 150 ms].…”
Section: Multiple-distractor Tasksupporting
confidence: 90%
“…Consistent with previous research (Bisley et al, 2004), the LIP population responses for both Target-In and Target-Out trials exhibited a very short latency of 47.5 ms. More importantly, both SUA and MUA discriminated between Target-In and Target-Out trials as early as 52.5 ms after stimulus onset (t test on the average SUA and MUA separately, p Ͻ 0.05), in line with the 50 ms selectivity latency of the fastest LIP neurons recorded by Buschman and Miller (2007). Our short population latencies were confirmed by calculations of the neural selectivity latencies (Target-In versus Target-Out) of individual recording sites (t tests on 20 ms bins): the fastest LIP neurons (fifth percentile) showed selectivity latencies of 50 ms [median selectivity latency: 150 ms].…”
Section: Multiple-distractor Tasksupporting
confidence: 90%
“…Interestingly, the LIP exhibits neuronal latencies to visual stimulation that are only slightly longer than in primary and secondary visual cortex and much shorter than in inferior temporal cortex, suggesting that it has privileged access to feedforward information (Bullier, 2001;Gottlieb et al, 1998). Thus, LIP shows a rapid on-response to any visual stimulus irrespective of its current relevance, followed by a later sustained activity which is sensitive to attentional modulations (Bisley et al, 2004). This pattern of response is reminiscent of the sequence of processing stages identified in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Recently it has been shown that the LIP area contains three signals (33-36): a bottom-up stimulus-onset signal, a saccade-related signal, and a cognitive, top-down signal that distinguishes targets from distractors. Interestingly, these different types of signals arrive at different latencies: The cognitive signal has latencies of about 117-133 ms, which is similar to our estimated delay for value processing (∼184 ms), but the visual signal is much faster, at ∼40 ms (33,34). In summary, the LIP area likely contains a priority map that integrates bottom-up and top-down information to guide visuospatial attention and eye movements (37,38).…”
Section: Discussionsupporting
confidence: 66%